PENGARUH PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENCAIRAN TUNGGAKAN PAJAK DI KANTOR PELAYANAN PAJAK MADYA PEKANBARU - Yohanes Diaken Nainggolan; Kamaliah Kamaliah; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine how much the influence of disbursement of tax arrears with a letter of reprimand against tax revenue in Tax Office of Pekanbaru and determine how much the influence of the forced tax collection by the letter of the tax revenue in Pekanbaru City Tax Office. The population in this study is a letter of reprimand and forced letter issued by the Tax Office Pekanbaru. Samples will be taken by the researchers is a letter of reprimand and forced letter issued by the Tax Office of Pekanbaru in 2011 until 2013 (3 years). Further analysis of data using multiple linear regression model. According to the partial test results can be concluded that the warning letter does not have a significant effect on the disbursement of tax arrears. It can be seen from the value t <t table so that Ho accepted and Hi rejected. Tests on forced letter, shows that these variables affect the disbursement of tax arrears that can be seen from the value t count> t table, so that Ho refused and H2 accepted. The magnitude of the effect of the warning letter and the letter forced to increase disbursement of tax arrears in KPP Madya Pekanbaru is 0.834 or 83.40%.Keywords: Billing, Disbursement Arrears, and Taxes